Chondroid syringoma of medial canthus – A rare case report (Indian Journal of Case Reports, 2020)
Chondroid syringoma of the skin is a rare, benign skin adnexal tumor, usually exhibited as a slowly growing intradermal or subcutaneous nodule, typically located in the head-and-neck region. Chondroid syringoma usually appears on the face; medial canthus being a rare site of predilection. The diagnosis is usually made retrospectively based on histological features of the surgically excised mass which is usually asymptomatic. We present a rare case of a 35-year-old man who presented with a painless, subcutaneous nodule in the medial canthus of the right eye. The diagnosis of chondroid syringoma was rendered. To the best of our knowledge, only one case of chondroid syringoma of the medial canthus has been documented in the literature. Histopathological examination is mandatory for arriving at the diagnosis. It should be considered in the differential diagnosis of all the slowly growing nodular lesions in the face.